Morphology of larvae and pupae of four species of Neotropical Acanthocinini (Cerambycidae, Lamiinae) - Casari, Sônia A.; Biffi, Gabriel; Nascimento, Francisco Eriberto L. (Zootaxa, 2025)
Acanthocinini is a tribe of Lamiinae with questionable monophyly and close affinity with Acrocinini and Colobotheini. Despite being the tribe with the largest number of known immature forms, it is poorly characterized, only by arbitrary features of adults. Here we describe and illustrate larva and pupa of four species of Acanthocinini: Baryssinus marisae Martins & Monné, 1974, Oedopeza umbrosa (Germar, 1823), Oxathres sparsa Melzer, 1927 (based on exuviae) and Xylergatoides asper (Bates, 1864), all but O. umbrosa, representing the first immature description of their genera.